Japanese encephalitis in children - Nurhayati Masloman; H S Widarso; W Cicilia (Indonesian Pediatric Society Publishing House, 2016)
Japanese encephalitis is a zoonotic disease caused by Japanese encephalitis virus, attacking domestic animals, mainly pigs and birds. It is transmitted to humans by mosquito bites, namely Culex tritaeniorhyncus.